ERRATA - Editoração, Núcleo de (Revista de Nutrição, 2023)
In article “Dairy products consumption in Brazil is associated with socioeconomic and demographic factors: Results from the National Dietary Survey 2008-2009”, with DOI: https://doi.org/10.1590/1678-98652017000100008, published in the Revista de Nutrição, 30(1):79-90, on page 89: Table 4, “%” should read “Mean”.